Effect of dringking water supplemented with wood vinegar on growth Performance and Carcass Characteristics in Muscovy duck - NORGERKHAMSAYSIONG, Seevone; KEOHAVONG, Bounmy; KHANDEE, Thanousin (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
These studies were to compere the different levels Wood vinegar on growth performance, feed intake, carcass characteristics and meat quality of Muscovy duck, this experiment was to conduced in the area of Souphanouvong University, Luang Prabang province, there were 4 treatments and design in CRD with 3 replications of each treatment. The treatments were: T1= 0%; T2= 0.5%; T3= 1% and T4= 1.5% of Wood vinegar (diluted with fresh water) this experiment was used 42 days, the result showed that: Used different levels of wood vinegar, there were no significant on final weight: T1= 2,260 g/head, T2= 2,193 g/head, T3= 2,127 g/ head and T4= 2,127 g/head, weight gain: T1= 1,340 g/head, T2= 1,273 g/head, T3= 1,207 g/head and T4= 1,207 g/head, average daily gain: T1= 31.90 (g/head/day), T2= 30.32 (g/head/day), T3= 28.73 (g/head/day) and T4= 28.73 (g/head/day) and feed conversion ratio: T1= 4.23, T2= 4.68, T3= 5.32 and T4= 4.60 (Pro>0.05), but intake of wood vinegar was significant and increasing of wood vinegar was reduse on feed intake on first period, but period 2 - period 6 (day 14-42) were no significant. Supplementation of wood vinegar were significant on live weight and carcass and was high when supplemted at 0.5% than 1 and 1.5% and when increasing level of wood vinegar was effect on live weight and reduded by increased the level of wood vinegar, but effect on overall on live weight and carcass characteristics (Pro<0.05). The carcass characteristics were significant (Pro<0.05) and reduded when increasing the level of wood vinegar, but wing, body frame were no significant (Pro>0.05). The inside of carcass characteristics were significant (Pro<0.05) such as: liver, bib bag, hearth, spleen, lung and when increasing the level of wood vinegar was reduded carcass.